Meta Analysis on Acceptance of Financial Technology in Islamic Perspective - Mimma Maripatul Uula; Syahdatul Maulida; Sherrindra Avedta (Ekonomi Islam Indonesia, 2022)
Fintech is a digital financial service innovation that can speed up financial inclusion in an age of ever-increasing technology progress. It turns out that even while the usage of fintech is increasing, many consumers are still unaware of or unable to utilize it appropriately. Many incidents of fintech misuse continue to occur, resulting in losses for individuals and businesses alike. To assess societal adoption of new technologies, the Technology Acceptance Model (TAM) has been established as an analytical tool. There are several studies on TAM in fintech, and the author uses a bibliometric technique to gather journal articles connected to the topic from the Dimensions website using VOSviewer in order to evaluate the data. The findings suggest that perceived usefulness and perceived ease of use have an impact on consumer choices when it comes to utilizing financial technology. Fintech service companies may utilize TAM analysis to better understand their customers' requirements and expectations. That means TAM will not only draw in new consumers, but keep current ones happy as well.